Therapy of the Hand and Upper Extremity Rehabilitation Protocols - Duncan, Scott F. M.; Flowers, Christopher W. (Springer International Publishing : Imprint: Springer, 2015)
Presenting over 100 rehabilitation protocols for the hand and upper extremity in an easy-to-use, step-by-step format, this practical reference provides surgeons and therapists alike with a go-to source for the therapy technique or strategy appropriate for their patients. Covering injuries from the shoulder, elbow, wrist, hand and fingers, each protocol includes bullet-pointed steps in daily or weekly increments following the injury or surgery and are inherently adaptable to the specific surgical intervention or rehabilitation requirement. Procedures following arthroplasty, extensor and flexor tendon injuries, fractures and dislocations, ligament and soft tissue injures, and nerve compression syndromes are among the many and multifaceted therapies presented. This book will be an invaluable resource for the orthopedic surgeon, hand surgeon, physical therapist, occupational therapist, hand therapist and any active clinician treating injuries to the hand and upper extremity.